PERAN PEMERINTAH DAERAH DALAM PEMBERDAYAAN INDUSTRI GENTENG DI KABUPATEN KEBUMEN - Bagus Daru Hari Respati; Budi Setiyono; Turtiantoro . (Journal of Politic and Government Studies, 2014)
The theme of entrepreneurship in the spotlight lately. Moreover, the industry is able to strengthen the local economy and reduce unemployment.This study aims to clarify the government's role in empowering the tile industry and identify the barriers tile employers and local governments in developing tile industry. The variables used in this study the role and empowerment of the tile industry. The method used is descriptive research type. In this study used descriptive research type because it can portray the condition in a systematic, factual and accurate information on the facts, including the ongoing process and the influence of phenomena that exist on the tile industry in Kebumen regency.The role of local government is crucial in empowering especially the tile industry that declined. The role of government in the empowerment consists of training, support tools, and marketing.Entrepreneurs perceived barriers are financial and non-financial issues, while the perceived barriers that local government communication and resource issues.